Congenital Anterior Urethral Obstruction: A Case Series - Shreelaxmi Madhusoodanan; Aravind C Soman; GM Asok Kumar; Hridya Menon (Journal of Clinical and Diagnostic Research)
Congenital Anterior Urethral Diverticulum (CAUD) and Anterior Urethral Valve (AUV) are rare but well-described causes of urinary obstruction in male children. The clinical presentation can range from isolated poor urinary stream with normal bladder and upper tracts to severe obstructive uropathy with renal failure. In the present case series, six children with anterior urethral obstruction managed between June 2014 and June 2024 were retrospectively identified. Age at presentation, clinical features, investigations, management and long-term follow-up were studied. The age at presentation ranged from newborn to seven years. Severe disease, as evidenced by progressive renal failure, was present in 1 of the 6 children (16.6%). One child had undergone foetal intervention by valve ablation but had progressive renal failure on follow-up. Three children (50%) underwent diverticulum excision with urethroplasty, of which one child developed a postoperative urethrocutaneous fistula. One child with AUV had a dorsal urethral fold causing obstruction, unlike the ventral pathology observed in the other children. CAUD and AUV are rare yet important causes of obstructive uropathy. Careful assessment is crucial for making the correct diagnosis. Temporary diversion may be essential when cystoscopy or primary repair is not feasible or in cases of urosepsis.